2012
DOI: 10.1007/s40136-012-0003-4
|View full text |Cite
|
Sign up to set email alerts
|

Topical Drug Delivery for Chronic Rhinosinusitis

Abstract: Chronic rhinosinusitis is a multifactorial disorder that may be heterogeneous in presentation and clinical course. While the introduction of endoscopic sinus surgery revolutionized surgical management and has led to significantly improved patient outcomes, medical therapy remains the foundation of long-term care of chronic rhinosinusitis, particularly in surgically recalcitrant cases. A variety of devices and pharmaceutical agents have been developed to apply topical medical therapy to the sinuses, taking adva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 95 publications
(102 reference statements)
0
22
0
Order By: Relevance
“…Clinical trials and meta-analyses have shown irrigation to be effective in reducing CRS symptoms and improving quality of life in both pre-surgical and post-operative periods 16 . This, together with its low-cost and favorable safety profile, makes nasal saline irrigation a robust choice for the management of sinonasal symptoms.…”
Section: Introductionmentioning
confidence: 99%
“…Clinical trials and meta-analyses have shown irrigation to be effective in reducing CRS symptoms and improving quality of life in both pre-surgical and post-operative periods 16 . This, together with its low-cost and favorable safety profile, makes nasal saline irrigation a robust choice for the management of sinonasal symptoms.…”
Section: Introductionmentioning
confidence: 99%
“…[42,43] Intranasal saline irrigation has been shown to increase drug delivery in comparison to the low sinus distribution efficiency of other methods, such as nasal sprays and nebulizers. [44–46] We therefore examined the ability of fluorescently labeled GM-0111 to be intranasally delivered in saline to mice.…”
Section: Resultsmentioning
confidence: 99%
“…In regard to the type of saline used, nasal irrigation with isotonic saline improves the nasal MCC of allergic patients due to changes in the rheological properties of mucous (33) and is better tolerated. Chusakul et al (23) investigated three types of isotonic saline solutions according to their alkalinity.…”
Section: Discussionmentioning
confidence: 99%